Response of Pasture Nitrogen Fertilization on Greenhouse Gas Emission and Net Protein Contribution of Nellore Young Bulls - Lima, Lais [UNESP]; Ongaratto, Fernando [UNESP]; Fernandes, Marcia [UNESP]; Cardoso, Abmael; Lage, Josiane; Silva, Luis; Reis, Ricardo [UNESP]; Malheiros, Euclides [UNESP] (MDPI, 2022)
This study aimed to evaluate the greenhouse gas (GHG) emission and net protein contribution (NPC) of Nellore young bulls grazing marandu palisade grass (Urochloa brizantha cv. Marandu) under three levels of pasture nitrogen (N) fertilization during backgrounding and finished on pasture or feedlot, based on concepts of sustainable intensification. The treatments were: System 1: pastures without N fertilizer during backgrounding, and animals finished on pasture supplemented with high concentrate at a rate of (20 g of concentrate per kg of body weight; P0N + PS); System 2: pastures fertilized with 75 kg N ha−1 year−1 during backgrounding and animals finished on feedlot fed a total mixed ration (TMR; P75N + F); and System 3: pastures fertilized with 150 kg N ha−1 year−1 during backgrounding, and animals finished on feedlot fed a TMR (P150N + F). During backgrounding, all pastures were managed under a continuous and put-and-take stock grazing system. All animals were supplemented with only human-inedible feed. Primary data from systems 1, 2 and 3, respectively, in the field experiment were used to model GHG emissions and NPC (a feed-food competitiveness index), considering the backgrounding and finishing phases of the beef cattle production system. Average daily gain (ADG) was 33% greater for the N fertilizer pastures, while carcass production and stocking rate (SR) more than doubled (P75N + F and P150N + F). Otherwise, the lowest GHG emission intensity (kg CO2e kg carcass−1) was from the P0N + PS system (without N fertilizer) but did not differ from the P75N + F system (p > 0.05; pastures with 75 kg N ha−1). The main source of GHG emission in all production systems was from enteric methane. Moreover, NPC was above 1 for all production systems, indicating that intensified systems contributed positively to supply human protein requirements. Moderate N fertilization of pastures increased the SR twofold without increasing greenhouse gas emissions intensity. Furthermore, tropical beef production systems are net contributors to the human protein supply without competing for food, playing a pivotal role in the food security agenda.
Keywords: feed conversion; greenhouse gases; human-edible protein; sustainability